Ecological Implications of Local Curriculum: Lessons Learned from a Participatory Action Research Project in a School in Nepal - Wagle, Shree Krishna (Dhaulagiri Journal of Sociology and Anthropology, 2023)
The dominant schooling design of the schools in Nepal celebrates Western-modern ideals of indoor schooling structure. The indoor design has continuously separated school education from the 'living' world. It has also constrained pedagogical innovations for outdoor teaching and learning. As textbook-based indoor teaching and learning has been culturally established as the standards of school education, despite several trainings and capacity development programs for headteachers and teachers, many schools in Nepal have not been able to address the intent of local curriculum for outdoor teaching and learning. Against this background, evidenced through the lessons learned from a Participatory Action Research (PAR) project for contextualized teaching and learning in a rural-located school in Nepal, this study portrays how the initiations for the local curriculum has been sandwiched in the limited space of linearly designed indoor pedagogical structure of the school. It argues the need to discover the ecological implications of the local curriculum. Following the transformative sustainability principles, the ecological implications suggest local curriculum practitioners revisit indoor schooling design and make it flexible to embrace community lifeworld as teaching and learning resources